Academic patronage in the Scottish enlightenment : Glasgow, Edinburgh and St Andrews universities - Emerson, Roger L. (Edinburgh University Press, 2008)
This book considers the politics of patronage appointments at the universities in Glasgow, Edinburgh and St Andrews, exploring the ways in which 388 men secured posts in three Scottish universities between 1690 and 1806. Most professors were political appointees vetted and supported by political factions and their leaders. This comprehensive study explores the improving agenda of political patrons and of those they served and relates this to the Scottish Enlightenment. Emerson argues that what was happening in Scotland was also occurring in other parts of Europe where, in relatively autonomous localities, elite patrons also shaped things as they wished them to be. The role of patronage in the Enlightenment is essential to any understanding of its origins and course. Key Features Based on considerable archival study, this book adds substantially to what is known about the Scottish professoriate during the period. A useful reference work on the universities, enriching our knowledge of them. Uncovers new information about the universities of Scotland during this period and about Scottish local and cultural politics more generally.